Chronic bird fancier's lung: histopathological and clinical correlation. An application of the 2002 ATS/ERS consensus classification of the idiopathic interstitial pneumonias. Issue 8 (1st August 2005) - Ohtani, Y; Saiki, S; Kitaichi, M; Usui, Y; Inase, N; Costabel, U; Yoshizawa, Y
Abstract : Background: Chronic bird fancier's lung (BFL) has often been misdiagnosed as one of the idiopathic interstitial pneumonias (IIPs). Methods: To define the clinical and pathological characteristics of chronic BFL, 26 patients with chronic BFL from whom a surgical lung biopsy specimen was taken between October 1992 and June 2001 were evaluated. The histopathological characteristics of the surgical lung biopsy specimens were examined and correlations between the histopathology and clinical characteristics were analysed. The quality of chronic inflammatory and fibrotic changes was expressed according to the 2002 ATS/ERS consensus classification of IIPs. Results: Two patients were diagnosed as having bronchiolitis obliterans organising pneumonia (BOOP)-like lesions, five as having cellular non-specific interstitial pneumonia (NSIP)-like lesions, and eight as having fibrotic NSIP-like lesions. The other 11 patients were considered to have usual interstitial pneumonia (UIP)-like lesions because of the temporal heterogeneous appearances of the fibrotic changes. However, fibrosis in these patients had developed in centrilobular as well as perilobular areas, suggestive of hypersensitivity pneumonitis. Nineteen patients (73.1%) had multinucleated giant cells, often with cholesterol clefts, while only five patients (19.2%) had granulomas. Patients with BOOP-like or cellular NSIP-like lesions tended to have recurrent acute episodes, whereas patients with UIP-like lesions had an insidious onset. Patients with BOOP-like or cellular NSIP-like lesions had a more favourable outcome than those with fibrotic NSIP-like and UIP-like lesions. Conclusions: The qualities of chronic inflammatory and fibrotic lesions vary significantly among patients with chronic BFL but correlate with clinical features and prognosis.